Dexmedetomidine Protects Against Lipopolysaccharide-Induced Acute Kidney Injury by Enhancing Autophagy Through Inhibition of the PI3K/AKT/mTOR Pathway - Zhao, Yuan; Feng, Xiujing; Li, Bei; Sha, Jichen; Wang, Chaoran; Yang, Tianyuan; Cui, Hailin; Fan, Honggang (Frontiers in Pharmacology, 2020)
Background. Acute kidney injury (AKI) is often secondary to sepsis. Previous studies suggest that damaged mitochondria and the inhibition of autophagy results in AKI during sepsis, but dexmedetomidine (DEX) alleviates lipopolysaccharide (LPS)-induced AKI. However, it is uncertain whether the renoprotection of DEX is related to autophagy or the clearance of damaged mitochondria in sepsis-induced AKI. Methods. In this study, AKI was induced in rats by injecting 10 mg/kg of LPS intraperitoneally (i.p.). The rats were also pretreated with DEX (30 μg/kg, i.p.) 30 min before the injection of LPS. The structure and function of kidneys harvested from the rats were evaluated, and the protein levels of autophagy-related proteins, oxidative stress levels, and apoptosis levels were measured. Further, atipamezole (Atip) and 3-Methyladenine (3-MA), which are inhibitors of DEX and autophagy, respectively, were administered before the injection of DEX to examine the protective mechanism of DEX. Results. Pretreatment with DEX ameliorated kidney structure and function. DEX decreased the levels of blood urea nitrogen (BUN) and creatinine (Cre), urine kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), reactive oxygen species (ROS), and apoptosis proteins (such as cleaved caspase-9 and cleaved caspase-3). However, DEX upregulated the levels of autophagy and mitophagy proteins, such as Beclin-1, LC3 II and PINK1. These results suggest that DEX ameliorated LPS-induced AKI by reducing oxidative stress and apoptosis and enhancing autophagy. To promote autophagy, DEX inhibited the phosphorylation levels of PI3K, AKT, and mTOR. Furthermore, the administration of Atip and 3-MA inhibitors blocked the renoprotection effects of DEX. Conclusions. Here, we demonstrate a novel mechanism in which DEX protects against LPS-induced AKI. DEX enhances autophagy, which results in the removal of damaged mitochondria and reduces oxidative stress and apoptosis in LPS-induced AKI through the α2-AR and inhibition of the PI3K/AKT/mTOR pathway.